2015
DOI: 10.1016/j.jfoodeng.2015.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Fresh-cut melon quality during storage: An NMR study of water transverse relaxation time

Abstract: a b s t r a c tMolecular mobility is a fundamental parameter which reflects the dynamic properties of food components and contributes to food degradation reactions comprehension. Fresh-cut fruits have become an important food market segment. However, processing of fruits promotes faster its physiological deterioration, biochemical changes and microbial degradation. The purpose of this work was to use NMR methodology as a tool to evaluate fresh-cut fruit quality, during storage at refrigerated conditions. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…In the present study, SSC values ranged between 6.85% and 9.57% Brix however except for Qilin, which recorded a significant increase on day 5 of storage there were no significant changes in SSC for the other cultivars throughout storage ( Table 1). The lack of significant change in SSC is consistent with the findings of Gil et al [20], Aguayo et al [22] and Fundo et al [23] who reported no significant differences in SSC of fresh-cut watermelon fruit and Amarillo melon during storage. The increase in SSC of Qilin could be attributed to the low juice leakage as well as reduced starch or sugar degradation considering the decreasing trend in respiration rate.…”
Section: Soluble Solids Content (Ssc) and Phsupporting
confidence: 91%
“…In the present study, SSC values ranged between 6.85% and 9.57% Brix however except for Qilin, which recorded a significant increase on day 5 of storage there were no significant changes in SSC for the other cultivars throughout storage ( Table 1). The lack of significant change in SSC is consistent with the findings of Gil et al [20], Aguayo et al [22] and Fundo et al [23] who reported no significant differences in SSC of fresh-cut watermelon fruit and Amarillo melon during storage. The increase in SSC of Qilin could be attributed to the low juice leakage as well as reduced starch or sugar degradation considering the decreasing trend in respiration rate.…”
Section: Soluble Solids Content (Ssc) and Phsupporting
confidence: 91%
“…The Aw of each 1 g sample was measured using a water activity meter (Aqualab Series 4TE, Decagon Devices Inc., Pullman, WA, USA) at 23 ± 2°C according to the method described by Fundo et al (2015). Each bacth was conducted in triplicate.…”
Section: Awmentioning
confidence: 99%
“…Water, accounting for 85%–90% of the fresh mushrooms, is held in more than one compartment based on the cellular structure and is a critical factor to maintain the quality of fresh mushrooms (Kumar et al , ; Paudel et al , ). Understanding changes in water mobility and location during storage is essential to explain the relation of moisture migration and the physico‐chemical quality of foods (Fundo et al , ; Fundo et al , ).…”
Section: Introductionmentioning
confidence: 99%